The effect of lengthening and shortening circle exercises with relative weights in developing the explosive ability of the two legs of young soccer players - علي فلاح محمد حسن, Hameed Majeed Hameed Abstract (Mustansiriyah Journal of Sports Science, 2024)
One of the most important factors that contributed to the development of sports is the development in the science of sports training, and the football game is one of these games that accompanied the development of the science of sports training. It is known that explosive ability is one of the most important physical characteristics that a football player needs, so he must Coaches should focus in their training on developing this important physical characteristic and use all means to assist in that, especially if we know that there are deficiencies in this characteristic among many players.The objectives of the research were the following:1- Developing a training curriculum using the method of lengthening and shortening to develop the explosive ability of the muscles of the legs for young soccer players.2- To identify the impact of the training curriculum using the method of the lengthening and shortening circuit with relative weights in developing the explosive ability of the two men for young soccer players.The researcher hypothesized that the training curriculum has a significant impact on developing the explosive ability of the two men for young soccer players.As for the second chapter, it included the research method, which is the experimental method, and the researcher chose the sample by the intentional method. The total sample reached (12) players. The chapter also contained the equipment and tools used, the exploratory experiment, the main experiment, and it also contained the prepared method, the tests used, and statistical methods.In the third chapter, the researcher, through tables and charts, presented the results of the pre and posttests by presenting the arithmetic mean and standard deviations, presenting and discussing the results of the (T-Test).The conclusions are:- The prepared curriculum has an impact on the development of the explosive strength of the muscles of the two legs for the control and experimental groups.- The use of auxiliary means has a better positive effect on the development of the level of explosive power.Through the conclusions of the research, the researcher recommends:- Using the prepared curriculum in addition to the means to help in developing explosive power.- Carrying out similar experiments and research on different samples.